AUTOMATIC REGULATION SYSTEM FOR SULFUR PURIFICATION OF NATURAL GAS - Sevinov J. U; Ashuraliyev A. A. (Research Parks Publishing LLC, 2021)
Algorithms for the synthesis of a fuzzy system for automatic control of natural gas desulfurization processes are presented. When forming the problem of analytical design of the regulator to control the temperature of the upper part of the column, the method of the minimum of the integral quality criterion was used. The presented results of mathematical and computer modeling showed that the designed optimal combined system can provide the required quality of the column temperature control process. The model parameters were estimated using the recursive filtering identification algorithm modified for the multidimensional case. In this case, the synthesis of a control algorithm consists of determining a control strategy that minimizes the variance of the controlled coordinate. The results of numerical analysis have confirmed their effectiveness, which makes it possible to use them in solving applied problems of optimizing the parameters of a combined fuzzy control system for the process of desulfurization of natural gas.